2018
DOI: 10.1016/j.rdc.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Methods to Advance Care, Diagnosis, and Therapy in Rheumatic Diseases

Abstract: This article provides an overview of the basis, usefulness, and validity of qualitative methods in research. It is aimed to enhance the understanding of a broad spectrum of readers, ranging from those mystified by such approaches, to those wanting a better critical knowledge to apply to literature review, and for health care providers considering developing an interest in the field. Qualitative research is crucial in augmentation of disease knowledge as well as the development of incremental care strategies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…This highlights how the accuracy of symptom-related reporting may be influenced by attention to language as well as physical and psychological context. [13][14][15][16][17] The multi-organ system involvement of SSc, as well as medication side effects, creates diverse and overlapping coincident manifestations and symptoms in a person living with SSc. These complicate perceptions of anticipated pulmonary symptoms.…”
Section: Symptomatology Of Interest To Measure In Ssc-ildmentioning
confidence: 99%
See 2 more Smart Citations
“…This highlights how the accuracy of symptom-related reporting may be influenced by attention to language as well as physical and psychological context. [13][14][15][16][17] The multi-organ system involvement of SSc, as well as medication side effects, creates diverse and overlapping coincident manifestations and symptoms in a person living with SSc. These complicate perceptions of anticipated pulmonary symptoms.…”
Section: Symptomatology Of Interest To Measure In Ssc-ildmentioning
confidence: 99%
“…We present seven overarching steps required to occur in robust PROM development ( 53,54 eliminates foundational steps and may not be sufficient to capture patient priorities and relevance to the particular disease experience. While PROMs with abbreviated development have utility in filling a care and research gap, optimal endpoint performance with robust methodology for patient content 16,55 remain an important concern especially for diseases like SSc-ILD that present assessment challenges.…”
Section: Path To Prom Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Background: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of diseases characterized by unknown origin arthritis that begins before the age of 16 years (1). Therefore, families are often affected by the disease of children.…”
mentioning
confidence: 99%
“…Background: Studies show that patients' biopsychosocial characteristics may be affected by various factors such as inpatient, outpatients, exercise intervention regularly. [1]. No studies have been found to examine this situation in the literature.…”
mentioning
confidence: 99%